GENDER : MENELAAH KEADILAN DAN KESETARAAN DALAM PERSPEKTIF ANTROPOLOGI - Hamid, Rahmat Zulfikar; Agustang, Andi; Idrus, Idham Irwansyah (Universitas Al Asyariah Mandar, 2023)
This paper discusses gender discourse, building justice and equality from an anthropological perspective. In critical studies, anthropology views that there are socio-cultural influences in building equality and justice in a multicultural society like in Indonesia. Gender itself is the behavior or division of roles between men and women that has been constructed or formed in the social environment. The anthropological approach views that gender differences are social constructions that are formed through social and cultural processes. In gender studies, researchers examine various social and cultural phenomena related to gender such as the distribution of gender roles, access to resources, and determining gender identity. This study also explores how gender differences impact the rights, opportunities and powers possessed by individuals and groups in society. The aim of gender discourse is to place men and women in a social framework in which they are both important components of that environment, rather than simply trying to understand them independently. Sometimes, considerations of socioeconomic class, ethnic differences, skin color differences, and religious differences contribute to the problem of social injustice in society. However, gradually this problem can be resolved with the birth of the General Declaration of Human Rights (UDHR) which guarantees many factors related -these factors. Then it is different with differences in sex or gender which are still considered unfinished. Problems regarding these differences do not only occur in underdeveloped and developing countries, but are also still one of the issues that are still being discussed in developed countries.